2015
DOI: 10.1016/j.urolonc.2014.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Clinically nonmetastatic renal cell carcinoma with sarcomatoid dedifferentiation: Natural history and outcomes after surgical resection with curative intent

Abstract: Purpose Renal cell carcinoma with sarcomatoid dedifferentiation (sRCC) is an aggressive malignancy associated with a poor prognosis. While existing literature focuses on patients presenting with metastatic disease, characteristics and outcomes for patients with localized disease are not well described. We aimed to evaluate post-nephrectomy characteristics, outcomes, and predictors of survival in patients with sRCC who presented with clinically localized disease. Patients and Methods An IRB-approved review fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
43
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 14 publications
4
43
0
Order By: Relevance
“…More recent studies with larger patient numbers identify thrombus present above the diaphragm as predictive of risk of perioperative complications but not of cancer outcomes . The presence of sarcomatoid features is predictive of poor cancer outcomes in non‐metastatic disease , but the lack of predictive significance in the present cohort may reflect the relatively few patients with sarcomatoid features.…”
Section: Discussionmentioning
confidence: 62%
“…More recent studies with larger patient numbers identify thrombus present above the diaphragm as predictive of risk of perioperative complications but not of cancer outcomes . The presence of sarcomatoid features is predictive of poor cancer outcomes in non‐metastatic disease , but the lack of predictive significance in the present cohort may reflect the relatively few patients with sarcomatoid features.…”
Section: Discussionmentioning
confidence: 62%
“…Zhang et al [20] suggested that PSD was an independent predictor of prognosis. However, the prognostic value of PSD in patients with RCC is still under debate [21,22]. Our study failed to include PSD in the multivariate analysis model due to insufficient data.…”
Section: Discussionmentioning
confidence: 97%
“…Specifically, the presence of sarcomatoid elements is associated with higher stage at presentation, aggressive disease course, and decreased patient survival, both in the localized and metastatic settings. [69] Although there have been multiple reports of various chemotherapeutic regimens in the literature, the response rates have been modest at best. [10, 11] Recently, several studies have reported the use of systemic targeted therapy in sRCC patients, however, response rates varied between 0% to 15.8% with no statistically significant differences between targeted agents and chemotherapy, indicating a need for better risk stratification.…”
Section: Introductionmentioning
confidence: 99%